I'm guessing you're given
![f(x)=\displaystyle\sum_(n=1)^\infty((-1)^n+1)(x-4)^n](https://img.qammunity.org/2020/formulas/mathematics/college/z5squim5542bg4re5r1u2pennoyr9m5fnq.png)
Note that for odd
, the corresponding term in the series is 0, so only the even terms matter. Let
, for which
. Then
![f(x)=\displaystyle2\sum_(k=1)^\infty(x-4)^(2k)](https://img.qammunity.org/2020/formulas/mathematics/college/2cvu9o5r26zesfarwb2xj9h034cefsrj1d.png)
Differentiating/integrating the power series gives
![f'(x)=\displaystyle4\sum_(k=1)^\infty k(x-4)^(2k-1)](https://img.qammunity.org/2020/formulas/mathematics/college/er7u8quszemgarn8fet82a5mqnj4dh964m.png)
![f''(x)=\displaystyle4\sum_(k=1)^\infty k(2k-1)(x-4)^(2k-2)](https://img.qammunity.org/2020/formulas/mathematics/college/khbjrl480cp10zc412bynwt6u9q1ajlj45.png)
![\displaystyle\int f(x)\,\mathrm dx=2\sum_(k=1)^\infty\frac{(x-4)}^(2k+1)}{2k+1}+C](https://img.qammunity.org/2020/formulas/mathematics/college/o2ooan65ztrf1x5lyenpxbt8jf2p7qkgw4.png)
By the ratio test, ...
a. ...
converges for
![\displaystyle\lim_(k\to\infty)\left|(2(x-4)^(2(k+1)))/(2(x-4)^(2k))\right|=|x-4|^2\lim_(k\to\infty)1=|x-4|^2<1](https://img.qammunity.org/2020/formulas/mathematics/college/j6xajnlylo5mvtr72s1xpehrw5a451ebac.png)
![\implies\boxed{3<x<5}](https://img.qammunity.org/2020/formulas/mathematics/college/8n0l996i49esnldgonvt8mtw74bc4chfor.png)
b. ...
converges for
![\displaystyle\lim_(k\to\infty)\left|(4(k+1)(x-4)^(2(k+1)-1))/(4k(x-4)^(2k-1))\right|=|x-4|^2\lim_(k\to\infty)\frac{k+1}k=|x-4|^2<1](https://img.qammunity.org/2020/formulas/mathematics/college/47ln0foye8zqqqm20ky227l24f3aghhg9z.png)
![\implies\boxed{3<x<5}](https://img.qammunity.org/2020/formulas/mathematics/college/8n0l996i49esnldgonvt8mtw74bc4chfor.png)
c. ...
converges for
![\displaystyle\lim_(k\to\infty)\left|(4(k+1)(2(k+1)-1)(x-4)^(2(k+1)-2))/(4k(2k-1)(x-4)^(2k-2))\right|=|x-4|\lim_(k\to\infty)((k+1)(2k+1))/(k(2k-1))=|x-4|^2<1](https://img.qammunity.org/2020/formulas/mathematics/college/1cgzy2ge85q7s7qcvprizcxv6i0kxi5fnd.png)
![\implies\boxed{3<x<5}](https://img.qammunity.org/2020/formulas/mathematics/college/8n0l996i49esnldgonvt8mtw74bc4chfor.png)
d. ...
converges to
![\displaystyle\lim_(k\to\infty)\left|\frac{2\frac{(x-4)}^(2(k+1)+1)}{2(k+1)+1}}{2\frac{(x-4)}^(2k+1)}{2k+1}}\right|=|x-4|\lim_(k\to\infty)(2k+3)/(2k+1)=|x-4|<1](https://img.qammunity.org/2020/formulas/mathematics/college/cgbkicdt7tere3x8kxvi0ed4bso6kmwzw4.png)
![\implies\boxed{3<x<5}](https://img.qammunity.org/2020/formulas/mathematics/college/8n0l996i49esnldgonvt8mtw74bc4chfor.png)